(3GdJcedI dhajGJ GdfbdIs - (3YHO GdYXje Hf YHO Gdbhj Hf YHO Gddg, CHh eMeO, Rcj GdOjf GdefPQj ,J (B656 (3g` s; (3eMeO Hf YHO Gddg Hf CMeO Hf QHjYI, CHh SdjeGf GHf RHQ GdQHYj,J (B379 (3g` s
(3ChdgG (B:s
(3jHJOF ajg HHbjI hajGJ Sf (B582 s
(3BNQgG (B:s
(3jfJgi HSfI (B642 s
(3JcQQ CjVkG JMJ Qbe (B" 626 " (3JGQjNs
(3Ydi GdfSNI NW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B97 s
Keywords: (3GdJGQjNs